If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1x + 6(6x + 2) = -2 + 7(-4 + 11) Reorder the terms: -1x + 6(2 + 6x) = -2 + 7(-4 + 11) -1x + (2 * 6 + 6x * 6) = -2 + 7(-4 + 11) -1x + (12 + 36x) = -2 + 7(-4 + 11) Reorder the terms: 12 + -1x + 36x = -2 + 7(-4 + 11) Combine like terms: -1x + 36x = 35x 12 + 35x = -2 + 7(-4 + 11) Combine like terms: -4 + 11 = 7 12 + 35x = -2 + 7(7) Multiply 7 * 7 12 + 35x = -2 + 49 Combine like terms: -2 + 49 = 47 12 + 35x = 47 Solving 12 + 35x = 47 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 35x = 47 + -12 Combine like terms: 12 + -12 = 0 0 + 35x = 47 + -12 35x = 47 + -12 Combine like terms: 47 + -12 = 35 35x = 35 Divide each side by '35'. x = 1 Simplifying x = 1
| 0.04(4-1)=0.03(-1+8)+0.04 | | h=40t-5t^2 | | 18x^2+23x-6=0 | | 17n=-4 | | -4(n+3)-6=-2(n-7) | | 4y^2+y-3=0 | | 7r^2+48r-7= | | -(x+11)=9 | | -3(-9+x)=24 | | 3(a+2)=2(a-7) | | 11(4x+11)=-2 | | -4(-3+x)=48 | | 4(x-5)=3x-8 | | 2(-4+a)=-24 | | 6x-7x=12 | | 8g+18=62 | | 2(3+k)=2 | | 8y+328=4y | | 3x+9=42 | | 3(-2-4)=2(5-2+1) | | 3c^2+25c+50=0 | | 11x-6=3x^2 | | 5=x+10 | | x^2-4x-21=fector | | x^4-4x^3-12x^2=0 | | 4/12= | | 5x+7.2=4x | | P^2+2p-8= | | 4x^2-24x+27=0 | | 5v^2+3=-8v | | w+16=-8 | | 3X+47=0 |